Antifungal Drug Repurposing - Jong H. Kim; Luisa W. Cheng; Kathleen L. Chan; Christina C. Tam; Noreen Mahoney; Mendel Friedman; Mikhail Martchenko Shilman; Kirkwood M. Land (MDPI AG, 2020)
Control of fungal pathogens is increasingly problematic due to the limited number of effective drugs available for antifungal therapy. Conventional antifungal drugs could also trigger human cytotoxicity associated with the kidneys and liver, including the generation of reactive oxygen species. Moreover, increased incidences of fungal resistance to the classes of azoles, such as fluconazole, itraconazole, voriconazole, or posaconazole, or echinocandins, including caspofungin, anidulafungin, or micafungin, have been documented. Of note, certain azole fungicides such as propiconazole or tebuconazole that are applied to agricultural fields have the same mechanism of antifungal action as clinical azole drugs. Such long-term application of azole fungicides to crop fields provides environmental selection pressure for the emergence of pan-azole-resistant fungal strains such as Aspergillus fumigatus having TR34/L98H mutations, specifically, a 34 bp insertion into the cytochrome P450 51A (CYP51A) gene promoter region and a leucine-to-histidine substitution at codon 98 of CYP51A. Altogether, the emerging resistance of pathogens to currently available antifungal drugs and insufficiency in the discovery of new therapeutics engender the urgent need for the development of new antifungals and/or alternative therapies for effective control of fungal pathogens. We discuss the current needs for the discovery of new clinical antifungal drugs and the recent drug repurposing endeavors as alternative methods for fungal pathogen control.